1988
DOI: 10.1152/jappl.1988.65.5.2313
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous hormones subtly alter women's response to heat stress

Abstract: The thermoregulatory responses of menstruant women to exercise in dry heat (dry-bulb temperature/wet-bulb temperature = 48/25 degrees C) were evaluated at three times during the menstrual cycle: menstrual flow (MF), 3-5 days during midcycle including ovulation (OV), and in the middle of the luteal phase (LU). Serum concentrations of estradiol-17 beta (E2), progesterone (Pg), luteinizing hormone (LH), and follicle-stimulating hormone (FSH) were measured by radioimmunoassay, and these values were used to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 0 publications
4
24
0
Order By: Relevance
“…Second, the CTM value of 40.4 1C was based on an exhaustive heat stroke model in rats, whereas many models and instances of heat stroke are of a passive nature (Chiu et al, 1995(Chiu et al, , 1996Haveman et al, 1996;Kao and Lin, 1996;Leon et al, 2005;Lin et al, 1994Lin et al, , 1997Liu et al, 2000;Romanovsky and Blatteis, 1996;Wilkinson et al, 1988;Wright, 1976;Wright et al, 1977). Third, noted species (Hutchison, 1961), strain (Furuyama, 1982), seasonal (Hoar, 1955;Hutchison, 1961), circadian (Hutchison, 1961;Kosh and Hutchison, 1968;Wright et al, 1977), photoperiod (Hutchison, 1961), geographic (Carter et al, 2005;Hutchison, 1961) and sex effects (Aoki et al, 1998;Carpenter and Nunneley, 1988;Furuyama, 1982;Lublin et al, 1995;Ohara et al, 1975;Mehnert et al, 2002) on heat susceptibility suggest that considerable variability of CTM will exist between studies depending on one or all of these factors. For example, the lowest observed CTM in passively heat stressed mice is 40.7 1C (unpublished observations).…”
Section: The Time-intensity Relationship Of Heat Exposurementioning
confidence: 99%
“…Second, the CTM value of 40.4 1C was based on an exhaustive heat stroke model in rats, whereas many models and instances of heat stroke are of a passive nature (Chiu et al, 1995(Chiu et al, , 1996Haveman et al, 1996;Kao and Lin, 1996;Leon et al, 2005;Lin et al, 1994Lin et al, , 1997Liu et al, 2000;Romanovsky and Blatteis, 1996;Wilkinson et al, 1988;Wright, 1976;Wright et al, 1977). Third, noted species (Hutchison, 1961), strain (Furuyama, 1982), seasonal (Hoar, 1955;Hutchison, 1961), circadian (Hutchison, 1961;Kosh and Hutchison, 1968;Wright et al, 1977), photoperiod (Hutchison, 1961), geographic (Carter et al, 2005;Hutchison, 1961) and sex effects (Aoki et al, 1998;Carpenter and Nunneley, 1988;Furuyama, 1982;Lublin et al, 1995;Ohara et al, 1975;Mehnert et al, 2002) on heat susceptibility suggest that considerable variability of CTM will exist between studies depending on one or all of these factors. For example, the lowest observed CTM in passively heat stressed mice is 40.7 1C (unpublished observations).…”
Section: The Time-intensity Relationship Of Heat Exposurementioning
confidence: 99%
“…O 2 max) and progressive high intensity running was unaffected by menstrual cycle phase (Lebrun et al 1995;Lynch and Nimmo 1998). However, very few studies (Horvath and Drinkwater 1982;Carpenter and Nunneley 1988;Stephenson and Kolka 1988) have examined performance in the follicular and luteal phases of the menstrual cycle in the heat, despite numerous international competitions being organised in hot climates. From the studies that have been undertaken it was concluded that cycling and walking performance were unaffected by menstrual phase.…”
Section: Introductionmentioning
confidence: 99%
“…From the studies that have been undertaken it was concluded that cycling and walking performance were unaffected by menstrual phase. In addition, it has been shown that during submaximal cycling in the heat for acclimatised subjects, deep body temperature may be higher during the luteal compared with the follicular phase (Carpenter and Nunneley 1988). For unacclimatised subjects reports are controversial, with deep body temperature reported to be higher (Stephenson and Kolka 1988) or unaffected by menstrual phase (Wells and Horvath 1974;Horvath and Drinkwater 1982).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of different hormone replacement therapies for middleaged women on the thermoregulatory system during rest and exercise in the heat have also been studied extensively during the last decade (3,4,8,25). Analysis of circulating estrogen and progesterone during heat stress showed that an increased progesterone-to-estrogen ratio during the luteal phase was associated with an elevated T c (5). However, elevated circulating levels of unopposed estrogen in middle-aged women at rest and during EHS were associated with a lower regulated T c (25).…”
mentioning
confidence: 99%